Rhythm versus rate control in patients with newly diagnosed atrial fibrillation: observations from the GARFIELD-AF registry. (3rd October 2022) - Pope, M K; Hall, T S; Atar, D; Virdone, S; Pieper, K; Jansky, P; Steffel, J; Haas, S; Gersh, B J; Goto, S; Panchenko, E; Baron-Esquivias, G; et al.
Abstract: Background: Atrial fibrillation is associated with considerable morbidity and mortality. Real-world reports on the effect of early rhythm control on patient outcomes in patient with recent onset atrial fibrillation are limited. Purpose: To assess the effect of early rhythm versus rate control on clinical outcomes in patients with newly diagnosed non-valvular atrial fibrillation. Method: The Global Anticoagulant Registry in the FIELD-AF (GARFIELD-AF) is a non-interventional registry of adult (≥18 years) patients with newly diagnosed atrial fibrillation (≤ six weeks' duration) and at least one investigator determined risk factor for stroke. Patients were enrolled in 1317 participating sites in 35 countries between March 2010 and August 2016. Patients with permanent atrial fibrillation were excluded. Stratification to rhythm or rate control was based on treatment strategy initiated at baseline (≤48 days post enrolment). Rhythm control was defined as investigator reported initiation of rhythm control (antiarrhythmic drug(s), cardioversion, or ablation – alone or in combination with rate modifiers). Rate control was defined as investigator reported initiation of rate control and absence of rhythm control therapy. Overlap propensity weighting and Cox proportional-hazards models were used to evaluate effect on outcomes. Results: Of 45, 382 included patients, 23, 858 (52.6%) received rhythm control and 21, 524 (47.4%) rate control. Rates of rhythm control were similar throughout the study time period (52.7% in 2010/2011, 54.2% in 2015/2016). Patients in the rhythm control group were younger (median age (Q1; Q3) 68.0 (60.0; 76.0) versus 73.0 (65.0; 79.0)), had lower rates of prior stroke/transitory ischemic attack/systemic embolism (9.4% vs 13.0%), and a lower median GARFIELD death score (4.0 (2.3; 7.5) versus 5.1 (2.8; 9.2)). Median CHA2DS2-VASc Scores were 3.0 (2.0; 4.0) in both groups. Rate of anticoagulation treatment was similar in the rhythm and rate control group (66.0% versus 65.5%). After propensity score overlap weighting, patients of the two groups were well balanced on all observed characteristics. Event rates per 100 person-years (95% confidence interval [CI]) over two years follow-up in the rhythm and rate control group were 2.94 (2.78–3.10) versus 4.43 (4.22–4.64) for mortality, 0.84 (0.75–0.92) versus 1.16 (1.05–1.27) for non-haemorrhagic stroke/systemic embolism and 0.84 (0.76–0.93) versus 1.16 (1.06–1.27) for major bleeding. Adjusted hazard ratios (95% CI) for the same time period were 0.85 (0.79–0.92), 0.84 (0.72–0.97) and 0.9 (0.78–1.04). Conclusion: In this large, internation registry, a rhythm control strategy was initiated at baseline in about half of the patients with newly diagnosed non-valvular atrial fibrillation. After adjustment for confounding factors, a significantly lower risk of all-cause mortality and non-haemorrhagic stroke/systemic embolism were observed for patients that received an early rhythm control strategy. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): This work was supported by the Thrombosis Research Institute (London, UK).